2013
DOI: 10.1007/s00445-013-0702-9
|View full text |Cite
|
Sign up to set email alerts
|

Storage and eruption of near-liquidus rhyolite magma at Cordón Caulle, Chile

Abstract: International audienceThe last three eruptions at the Cordón Caulle volcanic complex, Chile, have been strikingly similar in that they have started with relatively short pre-eruptive warning and produced chemically homogeneous rhyolite to rhyodacite magma with glassy to aphyric texture. These characteristics collectively call for an understanding of the storage conditions leading to the rise and extraction of crystal-poor silicic magma from volcanoes. We have analyzed and experimentally reproduced the mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
184
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(201 citation statements)
references
References 56 publications
15
184
0
2
Order By: Relevance
“…The 2011 eruption produced a rhyolite lava flow and pyroclastic flows close to the vent. It sent tephra to the SE to ESE, blanketing parts of the Chilean Andes, central Argentina, and the southern At-1 http://www.volcano.si.edu/volcano.cfm?vn=357150 lantic Ocean (Castro et al 2013). The axis of the tephra plume intersected Route 215 20 km southeast of the vent where tephra deposits were approximately 50 cm thick.…”
Section: Methodsmentioning
confidence: 99%
“…The 2011 eruption produced a rhyolite lava flow and pyroclastic flows close to the vent. It sent tephra to the SE to ESE, blanketing parts of the Chilean Andes, central Argentina, and the southern At-1 http://www.volcano.si.edu/volcano.cfm?vn=357150 lantic Ocean (Castro et al 2013). The axis of the tephra plume intersected Route 215 20 km southeast of the vent where tephra deposits were approximately 50 cm thick.…”
Section: Methodsmentioning
confidence: 99%
“…Shaw et al 1968;Walker 1971;Fink 1983;Webb and Dingwell 1990;Dragoni et al 1992;Manley 1992;Fink and Griffiths 1998;Manga et al 1998;Castro and Cashman 1999;Gottsmann and Dingwell 2001;Hess et al 2008;Castro et al 2013). It has been previously reported that the Rocche Rosse behaved as a Bingham fluid during emplacement (Clay et al 2013), which can promote strain localisation and folding.…”
Section: Crust Formationmentioning
confidence: 96%
“…Once the flow had cooled sufficiently, a brittle deformational phase dominated, and the flow no longer behaved as a viscous or ductile flow. (Carn et al 2009;Lara 2009;Castro et al 2013;Schipper et al 2013;Tuffen et al 2013). Recent active observations also give new perspectives on the formation of older rhyolitic lavas, such as the Rocche Rosse.…”
Section: Progressive Deformationmentioning
confidence: 96%
See 2 more Smart Citations